2017
DOI: 10.1007/s40685-017-0057-8
|View full text |Cite
|
Sign up to set email alerts
|

Tax certified individual auditors and effective tax rates

Abstract: This study examines how the appointment of tax certified individual auditors is associated with reported effective tax rates of corporate clients. The study uses a unique German institutional setting which makes it possible to track individual auditors that are also certified tax consultants and sign the audit opinion.Empirical results indicate that tax certified individual engagement partners are associated with higher effective tax rates. Further tests reveal that this association also exists for individual … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
1
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 77 publications
2
12
1
2
Order By: Relevance
“…We also found that the longer the auditor-client working relationship is, the more auditors can help clients to reduce tax expenditures. In fact, the outcomes of our second hypothesis are similar to Jeong and Bae (2013), Serafat and Barzegar (2015), Khajavi and Kiamehr (2015), Bae (2017), and Frey (2018). It seems that since most Iranian firms had financial stress due to pressures from economic sanctions between 2012 and 2017, they preferred to work with auditors for a long time so that auditors can provide appropriate mechanisms to reduce tax expenses because auditors have a better understanding of the client's working environment over time.…”
Section: Resultssupporting
confidence: 85%
“…We also found that the longer the auditor-client working relationship is, the more auditors can help clients to reduce tax expenditures. In fact, the outcomes of our second hypothesis are similar to Jeong and Bae (2013), Serafat and Barzegar (2015), Khajavi and Kiamehr (2015), Bae (2017), and Frey (2018). It seems that since most Iranian firms had financial stress due to pressures from economic sanctions between 2012 and 2017, they preferred to work with auditors for a long time so that auditors can provide appropriate mechanisms to reduce tax expenses because auditors have a better understanding of the client's working environment over time.…”
Section: Resultssupporting
confidence: 85%
“…This argument is the result of research by Salehi (2011), Habib (2012). However, some other studies such as Fengju et al (2013), Frey (2018) show a different result indicating that debt to total assets ratio (DAR) does not influence income smoothing. Habib (2012) states that the occurrence of income smoothing practices is also influenced by conflicts of interest between internal parties (management) and external parties (shareholders, creditors, and government).…”
Section: Introductionmentioning
confidence: 84%
“…The latter result, although theoretically convincing due to independence regulations on audit services, is somewhat surprising given the large literature on auditors trespassing their limited scope of function (Aobdia, 2015;Cai et al, 2016;Dhaliwal et al, 2016;McGuire, Omer, and Wang, 2012). Calibrating from the audit-firm level to the individual audit engagement partner, Frey (2018) suggests that the engagement of a German tax certified auditor, who signals high competency in taxes, is associated with higher effective tax rates at client firms. In contrast, Lim et al (2018), find that Chinese firms with stronger connections to low-tax firms through individual audit partners show lower effective tax rates.…”
Section: Channels For Tax Knowledge Diffusionmentioning
confidence: 98%
“…By examining a potential determinant of crosssectional variation in tax planning practices among firms, we follow the calls for contributions to the understanding of this matter (Cen et al, 2018;Dyreng and Maydew, 2017;Wilson, 2009). Recent research has turned to cross-firm connections, analyzing board ties (Brown, 2011;Brown and Drake, 2014), banks (Gallemore, Gipper, and Maydew, 2018), human capital turnover (Barrios and Gallemore, 2018), auditors (Frey, 2018;Lim et al, 2018) and the supply chain (Cen et al, 2017(Cen et al, , 2018. We extend this literature by analyzing the role of strategic alliances in tax knowledge diffusion.…”
Section: Introductionmentioning
confidence: 98%